Effect of magnetic field on mass transfer at ESA - Pereteatcu, P.; Ojegov, A.; Cracan, C.; Перетятку, Павло; Ожегов, Олександр; Кракан, Корнел (Харківський національний автомобільно-дорожній університет, 2024)
The study analyzed the effect of magnetic field (value and direction) on mass transfer at electro-spark alloying (ESA). It was experimentally established the increase the productivity of ESA process by additional action of the magnetic field.
Вплив магнітного поля на масообмін у процесі ЕIЛ
Keywords: electro-spark alloying; magnetic field; deposition; layer; electric discharge; електроіскрове легування; магнітне поле; осадження; шар; електричний розряд; 621.0.484.755; 10.30977/BUL.2219-5548.2024.107.0.21